Hi!
So we have to make a system of equations here.
Let sibling 1 be O and sibling 2 be Y (for older and younger)
So:
O + Y = 64
O = 64 - Y
(Either one works)
The older sibling is 6 years older.
O = Y + 6
Make everything in terms of Y.
64 - Y = Y + 6
Same to both:
58 = 2y
2y = 58
Divide by 2 on both sides:
y = 29
Since the older sibling is 6 years older:
29 + 6 = 35
Y = 29
O = 35
Let me know if you have any questions.
Step-by-step explanation:
It's telling you to plug in the numbers inside the parenthesis as x
Example: F(-1)= 2(-1)^3 -3(-1)^2 +7
Answer:
let the larger and smaller number be x and y respectively
first condition
x + y = 49
second condition
3x = 2y+97
3x-2y =97
Multiplying first condition by two and adding both equations
2x + 2y = 98
<u>3x -2y = 97</u>
5x = 195
x = 195/5 = 39
putting the value of x in
x + y = 49
y = 49 -39 = 10
again
Step-by-step explanation:
Answer:
4 and 9 hundreths
Step-by-step explanation:
Answer:
No, Angela is not correct.
As the method Jim was performing will also lead to the solution.
Step-by-step explanation:
We are given first equation as:
Ax + By = C
Second equation is:
Dx + Ey = F
Jim solved the equation as:
He begins by multiplying equation (1) by D and equation (2) by A.
and so by subtracting both the equations he will obtain a value of y.
and then put the y-value in any of the given two equations to obtain the value of x.
Angela Method:
you should have multiplied equation (1) by E and equation (2) by B.
and when she will subtract both the equations she will get the value of x first and then when she will put the value of x in any of the given equation she will obtain the value of y.
But both will get a value for x and y.
Hence, the method Jim was performing was also correct.